Effects of Intelligence Quotient, Emotional Quotient, and Motor Educability on Players Ability to Tact in Soccer Games (Journal of Physical Education and Sports, 2020)
Soccer requires athletes to have complete equipment in a game situation. Not only physical, mental, and technical aspects, but tactics must also be considered. The purpose of this research is to analyze the effect of intelligence quotient, emotional quotient, and motor educability on the ability of players to perform soccer tactics. This research is a quantitative descriptive study, a sample of 30 people with a sampling technique using a purposive sampling technique — data analysis using SPSS 22 application program, multiple linear regression analysis techniques. The results of the study did not have a significant effect between intelligence quotient and emotional quotient, and there is a significant influence between emotional quotient with motor educability, there is a significant influence between intelligence quotient and motor educability, intelligence quotient does not have a significant effect on a player's ability to engage in soccer tactics, emotional quotient does not have a significant effect on a player's ability to do soccer tactics, motor educability has a significant effect on a player's ability to do soccer tactics, intelligence quotient, emotional quotient, motor educability have a significant influence on the ability of players to do soccer tactics.